2014
DOI: 10.1371/journal.pone.0112861
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Human Papillomavirus Infection, Cervical Cancer and HPV Vaccination in North Indian Population

Abstract: BackgroundHuman Papillomavirus (HPV) -associated cervical cancer is the second-most common cancer in women worldwide but it is the most frequent gynaecological cancer and cancer associated death in India women. The objective of this study was to assess knowledge about cervical cancer, HPV, HPV vaccine, HPV vaccine acceptance among school and undergraduates students and their parent’s perception about acceptance of HPV vaccine in Northern part of India (Delhi and NCR regions).Materials and MethodsA qualitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
51
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 62 publications
6
51
2
Order By: Relevance
“…Direct comparison of the results of this survey with data of similar published results is complicated by the fact that the methodology vary between studies in terms of characteristics of each population, data collection, and ways of reporting. The level of knowledge is higher than those obtained in 18 to 25-year-old students in Germany which only 13.9% knew that HPV infection is sexually transmitted and <15% knew that HPV infects women and men, 33 in a group aged 18-24 in Singapore only 15.2% had ever heard of HPV, 31 in males aged 12-22 y in India respectively 31.5% and 28% were aware that HPV infection causes genital cancer and of availability of vaccine, 35 in the United Arab Emirates 31% of university students had not heard of HPV infection before, 34 in Hungary among adolescents 12 and 19 y only 35% have heard of the HPV and 46.6% knew that HPV infection may be transmitted by vaginal intercourse, 32 and in the US respectively 38.3% and 33.1% of respondents had heard of HPV and of the vaccine. 16 Not surprising only 4 students in this study have been vaccinated against HPV, but one important observation was that almost 2-thirds were likely to be vaccinated against HPV.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Direct comparison of the results of this survey with data of similar published results is complicated by the fact that the methodology vary between studies in terms of characteristics of each population, data collection, and ways of reporting. The level of knowledge is higher than those obtained in 18 to 25-year-old students in Germany which only 13.9% knew that HPV infection is sexually transmitted and <15% knew that HPV infects women and men, 33 in a group aged 18-24 in Singapore only 15.2% had ever heard of HPV, 31 in males aged 12-22 y in India respectively 31.5% and 28% were aware that HPV infection causes genital cancer and of availability of vaccine, 35 in the United Arab Emirates 31% of university students had not heard of HPV infection before, 34 in Hungary among adolescents 12 and 19 y only 35% have heard of the HPV and 46.6% knew that HPV infection may be transmitted by vaginal intercourse, 32 and in the US respectively 38.3% and 33.1% of respondents had heard of HPV and of the vaccine. 16 Not surprising only 4 students in this study have been vaccinated against HPV, but one important observation was that almost 2-thirds were likely to be vaccinated against HPV.…”
Section: Discussionmentioning
confidence: 64%
“…[29][30][31] Unfortunately all these issues among young males have only been studied to a limited extent. [32][33][34][35][36] Specifically in Italy, few studies have been conducted among different groups, [37][38][39] but to the authors' knowledge little is known to date regarding HPV vaccination in young males. It remains imperative this evaluation in order to identify information needs and to design future strategies for expanding cancer prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Hussain et al represents that overall HPV vaccine awareness is very low both in female and male as well as dwellers of rural and urban origin. 19 But in contrast, few studies reported that high vaccine acceptance among parents and adolescents in the general population. [20][21][22][23][24] A study by Massey et al indicated low awareness of HPV; among those who had heard of HPV, just 28% were willing to receive the HPV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of cervical cancer in women is rising each year, and it has become a large threat to women's health and a substantial burden on the global economy (Hussain et al, 2014;Skaaby et al, 2014). Its morbidity and mortality have remained at high levels in China (Du et al, 2014;Xu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%